Bacterial persistence: a cellular phenotype of clinical significance in chronic and recurrent infections - Suclupe-Campos, Danny-Omar (2020)
Persistent bacteria are the transient variants of a genetically homogeneous population generated by exposure to stress as in antibiotic treatment. They are an epigenetic phenomenon or a non-inherited phenotype, which may be considered as the first line of defense before developing antimicrobial resistance. Despite their discovery more than 70 years ago, their definition, mechanisms of formation, classification and morphologies of clinical implication are still current research topics. In the present research, we describe the relationship between chronic persistent infections and the formation of biofilms as important factors in recurrences, relapses and greater virulence in infections. Likewise, a brief review of the various mechanisms involved in bacterial persistence, their ineffective elimination due to antibiotic tolerance, and possible treatment strategies is provided. Overall, it is believed that persistence poses a significant burden of public health care. It is estimated that up to 10 million people will be yearly affected by 2050. Thus, a better comprehension of this bacterial phenotype is essential to fight against pathogenic bacteria and improve therapeutic results in the future.